Intergenerational transmission of values in the modern multicultural world - B. A. Vyatkin; V. Yu. Khotinets; O. V. Kozhevnikova (Obrazovanie i Nauka)
Introduction. The problem of the digital divide between different generations and the aggravation of intergenerational relations was one of the most debated in modern science. The key question is how modern social institutions (family, educational system) ensure the socialisation of the child in a new social situation of development, the transfer of cultural experience in the modern digital world. The urgency of the problem is heightened by the fact that in ethnically homogeneous regions of the Russian Federation, the strategies to transfer traditional values and cultural practices of a collectivist orientation to the younger generation are being maintained, contrary to the “model of desired future” with the successful autonomous behaviour of a sovereign person proposed by the new reality.Aim. The current research aims to explore the socio-psychological patterns of the value transmission in modern families from ethnically homogeneous regions. The study involved representatives of the autochthonous peoples of the Kama region (Udmurts, Komi-Permyaks, Tatars, Bashkirs, Russians) of the older generation – mothers (N = 173, average age 41.4), the younger generation – adolescents (N = 218; average age 14.5, 52.8% females).Methodology and research methods. The theoretical and methodological framework of the research is based on the theory of cultural value orientations, which determine the ways to solve basic problems in regulating human activity (S. Schwartz); the concept of ecological systems explaining the processes of value transmission in the interaction of a child with the outside world (U. Bronfenbrenner). To test the theoretical model, the Structural Equation Modelling method was used. To measure cultural values, a questionnaire for diagnosing cultural values constructed by S. Schwartz in the adaptation of V. N. Karandashev was used; to measure mother-to-child relations, the authors used the questionnaire “Child-Parental Relations of Adolescents” by O. A. Karabanova and P. V. Troyanovskaya; the features of intergenerational interaction in the family (mother-to-child) was studied using the questionnaire “Parent’s Interaction with a Child” by I. M. Markovskaya in two versions – for adolescents and mothers.Results. On the territory of the Russian Federation, stable patterns of value transmission based on traditional collectivist orientations, are preserved. Benevolence (kindness) holds its priority in the hierarchy of values and becomes a significant predictor of intergenerational interaction. At the same time, adolescents are transmitted with active patterns of behaviour to expand their opportunities to enter a world of fierce competition with growing uncertainty and high risks. The identified “clashes” in intergenerational interaction are explained by age patterns in the relationship between parents and adolescent children.Scientific novelty. The obtained results indicate a peculiar integration of collectivist values-goals and individualistic values-means among representatives of the autochthonous peoples of Russia. Models of the intergenerational transmission of values of mothers and adolescents have been constructed and explained revealing the patterns of the transfer of cultural experience in multicultural regions of the Russian Federation.Theoretical significance of the obtained results lies in the possibility of expanding the existing knowledge about the features of the digital generation socialisation in the context of traditional inculturation, about the transformation of the social situation of the development of a growing person in the focus of a new reality and the possibility of interaction between generations of “different worlds”.Practical significance of the acquired knowledge is revealed in the possibility of using it for constructing modern concepts of education and development of psychological and pedagogical technologies for socialising a growing person in the context of epoch-making trends.